2000
DOI: 10.1007/bf02461555
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing learning in science—Young children's responses to a classroom sequence on evaporation

Abstract: Five year old children's ideas were tracked by a range of means during and subsequent to a classroom sequence on evaporation. They held a range of conceptions which changed in complex ways across context and time. These could only be made sense of by moving outside traditional conceptual change interpretations to include broader notions of appropriation of language as a cultural tool, of personal and social narrative responses to features of the phenomena and the classroom setting, and the nature of science ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…In working with 3 to 6 year olds, Smith (2001) described how the active involvement of young children in gaining science knowledge is naturally motivating (Conezio & French, 2002) if topics are approached with sufficient depth and time, a position consistent with the 1995 National Science Education Standards (Rakow & Bell, 1998). In other representative work, Gould et al (2003) described an approach for early science instruction with gifted students; Tytler and Peterson (2000) summarized the meaningful changes in 5-year-olds' explanations of evaporation as a result of extended in-depth science instruction; Jones and Courtney (2002) addressed the processes of curricular planning for instruction and assessment in early science learning; Armga et al (2002) and Colker (2002) suggested guidelines for teaching science in early childhood settings; and Lee, Lostoski, and Williams (2000) described the benefits of schoolwide thematically-oriented instruction in science.…”
Section: Discussionmentioning
confidence: 99%
“…In working with 3 to 6 year olds, Smith (2001) described how the active involvement of young children in gaining science knowledge is naturally motivating (Conezio & French, 2002) if topics are approached with sufficient depth and time, a position consistent with the 1995 National Science Education Standards (Rakow & Bell, 1998). In other representative work, Gould et al (2003) described an approach for early science instruction with gifted students; Tytler and Peterson (2000) summarized the meaningful changes in 5-year-olds' explanations of evaporation as a result of extended in-depth science instruction; Jones and Courtney (2002) addressed the processes of curricular planning for instruction and assessment in early science learning; Armga et al (2002) and Colker (2002) suggested guidelines for teaching science in early childhood settings; and Lee, Lostoski, and Williams (2000) described the benefits of schoolwide thematically-oriented instruction in science.…”
Section: Discussionmentioning
confidence: 99%
“…From their early years, children develop their knowledge, values and ways of reasoning in relation to the world they live in. This development is influenced by different factors, the most important of which are direct sensory experience and the participation in everyday social life and in formal education (Matthews, 1994;Fleer & Robbins, 2003;Tytler & Peterson, 2001). Education, from the early years, has a fundamental role to play in providing children with problem recognition and solving skills and encouraging behaviours that are compatible with environmental quality preservation (Sheehy et al, 2000) as well as sustainable use of natural resources, such as water.…”
Section: Introductionmentioning
confidence: 99%
“…In most instances interviews have been used as the major means of data collection. In addition, many of these studies have investigated broader but related topics such as the water cycle, evaporation or weather, with children in a variety of cultural contexts, including the United States of America (Stepans & Kuehn, 1985), Israel (Bar, 1989), the United Kingdom (Dove, 1998;Russell et al, 1993), Botswana (Taiwo et al, 1999), Greece (Spiropoulou et al, 1999) and Australia (Tytler, 2000;Tytler & Peterson, 2000). Most of these studies draw heavily on the work of Piaget and others who have been influenced by Piagetian thought, particularly his early twentieth century investigations of children's conceptions of meteorology and the origin of water (Piaget, 1973).…”
Section: Previous Research On Children's Understandings Of Rain and Cmentioning
confidence: 98%